Computational assessment of hypoglycemic potency and ADMET evaluation of Alpinia galanga bioactive compounds against the alpha-glucosidase enzyme - Putra, Wira Eka; Sustiprijatno, Sustiprijatno; Hidayatullah, Arief; Widiastuti, Diana; Heikal, Muhammad Fikri (Eclética Química, 2026)
Alpha-glucosidase is known as a catabolic enzyme for carbohydrates which determine the glucose level in body. Therefore, inhibiting the activity of alpha-glucosidase should reduce the glucose plasma level. Thus, we aimed to evaluate the antidiabetic potency of bioactive Alpinia galanga compounds against alpha-glucosidase through an in silico approach. To a greater extent, the 2D structure of the ligands was retrieved from the PubChem database, and the 3D structure of alpha-glucosidase was built on the SWISS-MODEL website. Furthermore, pharmacokinetics analysis was performed via the pkCSM webserver. Interestingly, we showed that the potential interactions of α-bergamotene, β-farnesene, β-bisabolene, galangal acetate, and β-pinene were more significant than those of miglitol within the binding site region of alpha-glucosidase. This present study demonstrated that numerous bioactive compounds of Alpinia galanga have potential as antidiabetic agents based on the molecular docking and pharmacokinetics prediction. Thus, we suggest that the bioactive compounds of Alpinia galanga may be effective as alpha-glucosidase inhibitors. However, further comprehensive studies are needed to evaluate their biological effects, effectiveness, and efficacy.